2003
DOI: 10.1097/01.inf.0000065690.64686.c9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in very low birth weight preterm infants

Abstract: We found that the rate of VUR was lower in very low birth weight premature newborns than that reported in the medical literature among term newborns who developed UTI. VUR was less frequent in extremely low birth weight infants who developed UTI than in infants weighing 1001 to 1500 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 17 publications
8
36
1
6
Order By: Relevance
“…The overall incidence of UTI in VLBW is reported at 8.1%, stratified as 5.7% for infants weighing 1000 to 1500 g and increasing to 12.5% for those <1000 g. 43 Depending on the organism, at least 100 colony-forming units (CFU) ml -1 from a suprapubic bladder aspiration or 10 000 CFU ml -1 from a sterile bladder catheterization is required for diagnosis, or less for Gram-negative organisms or fungi. 43,44 Evaluation for a UTI is not indicated for VLBW infants in the first 72 h of life. 45 However, beyond this period, when urine is no longer considered sterile, it should be included in the evaluation of a symptomatic infant.…”
Section: Types Of Infectionsmentioning
confidence: 99%
“…The overall incidence of UTI in VLBW is reported at 8.1%, stratified as 5.7% for infants weighing 1000 to 1500 g and increasing to 12.5% for those <1000 g. 43 Depending on the organism, at least 100 colony-forming units (CFU) ml -1 from a suprapubic bladder aspiration or 10 000 CFU ml -1 from a sterile bladder catheterization is required for diagnosis, or less for Gram-negative organisms or fungi. 43,44 Evaluation for a UTI is not indicated for VLBW infants in the first 72 h of life. 45 However, beyond this period, when urine is no longer considered sterile, it should be included in the evaluation of a symptomatic infant.…”
Section: Types Of Infectionsmentioning
confidence: 99%
“…1, 8 Bauer reported that the prevalance of UTI among late-onset sepsis neonates with birth weight =1000 grams was 12.2%, while in neonates with birth weight 1001-1500 grams was 5.2%. 8 In our study, UTI was found in 3 out of 9 subjects with birth weight <1500 grams and in 3 out of 17 subjects with birth weight 1500-2499 grams, while in neonates with birth weight 2500-3999 grams was only 1 out of 21 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…7 Bauer et al reported 12.2% subjects with UTI among 279 late-onset sepsis neonates (gestational age of 26 ± 1.7 week). 8 Visser and Hall found 7.4% subjects with UTI from 189 neonates (gestational age 33.2 ± 1.1 weeks) who underwent sepsis evaluation for suspected late-onset sepsis. 4 Purniti reported UTI in 10 out of 35 preterm and 9 out of 52 term neonates with neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary tract infections occur in about 1% of term neonates, with a higher prevalence among preterm neonates. 6 Bacteria that commonly cause urinary tract infections, such as Escherichia coli, Klebsiella, and Enterobacter, travel from the gastrointestinal tract and anogenital area into the urinary tract. 7 In this case, L. lactis was thought to have come from the gastrointestinal tract after ingestion of the mother's breast milk.…”
Section: Discussionmentioning
confidence: 99%